Desafios de inovação tecnológica para o setor vitivinícola na Serra Gaúcha - Teixeira Junior, Jorge Luiz Jardim (My University, 2022)
Technological innovation is essential for the development of an industry. However, innovating to solve bottlenecks involves investments, knowledge and risks that can impede research or implementation of innovations in the market. The research aimed at obtaining technological solutions inherent to the wine sector in Brazil is still incipient and inconclusive, especially in aspects that refer to the advancement of productivity, competitiveness or diversity in the cultivation of wine grapes and the winemaking process. Therefore, the objective of this research was to map technological and productive bottlenecks, exploring their antecedents and consequences. This mapping was done from in-depth interviews with agricultural technicians and oenologists from one of the main wineries cooperatives in the Serra Gaúcha region, in addition to two wineries, one medium and one large. The result obtained was organized according to the degree of productivity, the number and size of grape producers, the type of target audience to which the final product is destined, the level of management knowledge and handling techniques used. Such information is more detailed in this research and will have summary relevance in proposing actions by government, companies and scientific institutions, to foster research and development, to seek technological innovation improvements for the sector and, consequently, -the most competitive. [resumo fornecido pelo autor]
A inovação tecnológica é fundamental para o desenvolvimento de um setor. No entanto, inovar para solucionar gargalos envolve investimentos, conhecimento e riscos que podem impedir a realização de pesquisas ou implementação das inovações no mercado. A pesquisa voltada à obtenção de soluções tecnológicas inerentes ao setor vitivinícola no Brasil ainda é incipiente e inconclusiva, especialmente nos aspectos que se referem ao avanço da produtividade, competitividade ou diversidade de cultivo de uvas viníferas e processo de vinificação. Sendo assim, o objetivo desta pesquisa foi mapear os gargalos tecnológicos e produtivos, explorando os seus antecedentes e as suas consequências. Este mapeamento foi feito a partir de entrevistas em profundidade com técnicos agrícolas e enólogos de uma das principais cooperativas vinícolas da região da Serra Gaúcha, além de duas vinícolas, uma de médio outra de grande porte. O resultado obtido foi organizado de acordo com o grau de produtividade, o número e porte dos produtores de uva, o tipo de público-alvo a qual o produto final é destinado, o nível de conhecimento de gestão e técnicas de manejo utilizados. Tais informações estão mais bem detalhadas nesta pesquisa e terão relevância sumária na proposição de ações de governo, empresas e instituições científicas, para o fomento na realização de pesquisas e desenvolvimento, para a busca de melhorias de inovação tecnológica para o setor e, consequentemente, tornando-o mais competitivo. [resumo fornecido pelo autor]
Keywords: Inovações tecnológicas; Vitivinicultura - Serra, Região (RS); Biotecnologia; Technological innovations; Viticulture - Serra, Region (Brazil); Biotechnology